ANALISIS YURIDIS PUTUSAN LEMBAGA ADAT ACEH DALAM PENYELESAIAN SENGKETA PEMBAGIAN WARISAN DI KOTA BANDA ACEH - RIFQAH SESARINA (PREMISE LAW JURNAL, 2013)
ABSTRACT   In Article 98, Paragraph 2 of Law No. 11/2006 on Aceh Administration states that the resolution of the problem of social condition in adat way is done through an adat body. The result of the research showed that the reason of the Aceh community in Bandah to have Aceh Adat Body as the place where they can settle the dispute in the distribution of inheritance because the resolution through negotiation in the level of gampong voluntarily in its process, on target procedure, the decision is not like the ruling of the Court (win or lose). The mechanism of the resolution of the dispute in the distribution of inheritance by Adat Body in Banda Aceh is done through a process which involves the Gampong Adat Body such as keuchik and other Gampong apparatus.  In practice, the implementation of the decision of Aceh Adat Body in settling the dispute in distributing inheritance in Banda Aceh is regarded as a judge’s verdict which is prevailing and binding the parties or the heirs who are in dispute.     Keywords: Adat Body, Dispute in Inheritance, Resolution of Dispute